The C4 protein encoded by tomato leaf curl Yunnan virus reverses transcriptional gene silencing by interacting with NbDRM2 and impairing its DNA-binding ability - Mei, Yuzhen; Wang, Yaqin; Li, Fangfang; Zhou, Xueping (PLoS pathogens, 2020)
In plants, cytosine DNA methylation is an efficient defense mechanism against geminiviruses, since methylation of the viral genome results in transcriptional gene silencing (TGS). As a counter-defense mechanism, geminiviruses encode viral proteins to suppress viral DNA methylation and TGS. However, the molecular mechanisms by which viral proteins contribute to TGS suppression remain incompletely understood. In this study, we found that the C4 protein encoded by tomato leaf curl Yunnan virus (TLCYnV) suppresses methylation of the viral genome through interacting with and impairing the DNA-binding ability of NbDRM2, a pivotal DNA methyltransferase in the methyl cycle. We show that NbDRM2 catalyzes the addition of methyl groups on specific cytosine sites of the viral genome, hence playing an important role in anti-viral defense. Underscoring the relevance of the C4-mediated suppression of NbDRM2 activity, plants infected by TLCYnV producing C4(S43A), a point mutant version of C4 unable to interact with NbDRM2, display milder symptoms and lower virus accumulation, concomitant with enhanced viral DNA methylation, than plants infected by wild-type TLCYnV. Expression of TLCYnV C4, but not of the NbDRM2-interaction compromised C4(S43A) mutant, in 16c-TGS Nicotiana benthamiana plants results in the recovery of GFP, a proxy for suppression of TGS. This study provides new insights into the molecular mechanisms by which geminiviruses suppress TGS, and uncovers a new viral strategy based on the inactivation of the methyltransferase NbDRM2.